McKenzie’s method effectiveness in patients with cervical vertebral pain. Chambas, Ciego de Ávila, 2022-2023 - Onesio Esteban de León Gutierrez; Israel Triana Pérez; Tania Alemán Martínez; Aray Pérez Pino; Félix Jorge Jiménez Cantero; Iván Castillo Ledo (Medisur, 2024)
Foundation: the McKenzie method is an examination and treatment system that places self-treatment at the center of the therapeutic strategy; it is a simple and easy way to reduce spinal pain, as well as quickly restore function and independence. Objective: to determine the McKenzie’s method physical exercises therapeutic effectiveness in patients with cervical vertebral pain. Methods: pre-experimental study, with pre-test and post-test, carried out in 64 patients with cervical vertebral pain of non-traumatic origin, who attended the Physiatrist consultation at the Julio Castillo and Camilo Cienfuegos polyclinics, in Chambas municipality, Ciego de Ávila province, from 2022 to 2023. The McNemar non-parametric test and the Wilcoxon Signed Rank Test were applied. Results: a greater number of patients were concentrated in the age groups from 30 to 39 years old (34.40%) and from 40 to 49 years old (39.10%). The female sex prevailed, with 71.90%. The most frequent etiologies were osteoarthritis and inadequate posture; and as the predominant symptom, pain radiating to the upper limbs. Furthermore, pressure pain predominated in all patients. Most required more than five treatment sessions to initiate pain relief. The pain intensity varied from severe to moderate in 82.8% of the cases, to mild-no pain in more than half of the patients (84.40%). Conclusions: the McKenzie Method was effective in reducing the pain intensity in patients with cervical vertebral pain.